Integration Moral Values through Dramaturgy in Dulmuluk Theater: A Study on Its Educational Impact - Notosutanto Arhon Dhony, Nugroho; Wadiyo, Wadiyo; Sahid, Nur; Cahyono, Agus (Journal of Education Culture and Society, 2025)
Aim. Dulmuluk theater, originating in Palembang, South Sumatra, is a traditional performance art inspired by King Ali Haji's poems, especially Abulmuluk and Siti Zubaidah. Focused on the transliterated Abulmuluk poem, its scripts adapt and develop this work. Early performances lacked written dialogues, relying on directors’ story outlines and actors' improvisations. Themes centre on tradition, blending Malay and Palembang regional languages.Methods. This research uses a type of phenomenological qualitative research method. Phenomenological qualitative research prioritises the subjective experiences of the various subjects encountered. Phenomenological qualitative research is a phenomenological study to describe the general meaning of a number of individual participants as subjects of various life experiences related to social and humanities concepts and phenomena.Results. The results of this study attempt to explore and analyse the study of dramaturgy in terms of the dramatic structure contained in the Abdulmuluk Jauhari play, the approach to Education of Budi Pekerti (religiosity, sociality, gender, justice, democracy, honesty, independence, fighting power, and responsibility).Conclusion. This study examines the moral education values embedded in Dul Muluk theater, which is used as an educational medium in schools. These values include religiosity (faith in religious teachings), sociality (care and empathy for others), gender equality (equal rights for men and women), justice (fairness in accommodating different abilities), democracy (role allocation based on competence), honesty (trustworthiness in words and actions), independence (confidence in decision-making and self-awareness), resilience (perseverance in facing challenges), and responsibility (accountability for actions and consequences).